Perception of Dasawisma Members on Innovation in Making of Nutrition Parks in PKK Food Program at the Jorong Parak Lubang - Jeniati, Kharisa; ‘Aini, Wirdatul (SAINTIS Publishing, 2019)
This study is motivated by the success of innovation in the making of nutrition parks in the Family Empowerment and Welfare (PKK) Food Program in Jorong Parak Lubang Nagari Tanjuang Gadang in Lima Puluh Kota Regency. This study aims to describe the perceptions of dasawisma members on the innovation of making nutritional parks in PKK food programs which are seen from five characteristics of innovation: relative benefits, level of suitability, level of complexity, can be tried, the slow pace of results seen. This type of study is quantitative descriptive study. The population in this study were 80 people. The sample in this study was taken 50% of the population, namely 40 dasawisma members using cluster random sampling technique. Data collection techniques used are questionnaires or questionnaires, while data analysis uses a percentage formula. The results showed that the perceptions of dasawisma members on the innovation of nutrition parks making activities on PKK food programs seen from (a) relative benefits showed very good, (b) the level of suitability showed very good, (c) the level of complexity showed very good, (d) can be tried showing very well, (e) the slow pace of results seen very good shows.